The Relationship of Education, Early Initiation of Breastfeeding and Parity with the Success of Exclusive Breastfeeding at the Muara Burnai Health Center, Lemrub Jaya District, Ogan Komering Ilir Regency 2021 - Suhartini Suhartini; Helni Anggraini; Satra Yunola (Science Midwifery, 2022)
Background: One way to reduce the infant mortality is through the Early Initiation of Breastfeeding (EIB) and continued with the exclusive breastfeeding until the baby reaches 6 months old. The Government Regulation No. 33 of 2012 instructs the Local Governments and the Private Sectors to work together to encourage the exclusive breastfeeding and early initiation of breastfeeding (EIB). Through the Government Regulations, the government formalizes the women's right to breastfeed (including at the workplace) and bans the promotion of breast milk substitutes. The objective of this study was to know the relationship of education, EIB, and parity with the exclusive breastfeeding. The research design used in this study was the analytical survey method with the cross sectional design. The population in this study contained 76 mothers having babies aged 7-12 months at the work area of ​​Puskesmas Muara Burnai, Lemembu Jaya District, Ogan Komering Ilir Regency, who were successful in giving the exclusive breastfeeding. Based on the results of the study that used the chi-square statistical test, it was found that there was a significant relationship between education and exclusive breastfeeding with the p. value = 0.001, there was a significant relationship between EIB and exclusive breastfeeding with the p. value = 0.000, there was a significant relationship between parity and exclusive breastfeeding with the p. value = 0.002. It could be concluded that there was a significant relationship between education, EIB, and parity with exclusive breastfeeding. It is recommended that the health workers at Puskesmas Muara Burnai,